دراسة كمومية لتشوه جزيء الإيتان وبعض مشتقاته أثناء الدوران الداخلي - بدوي محمد (Latakia University Journal -Basic Sciences Series, 2018)
استنادا إلى النظرية الميكانيكية الكمومية التقريبية حول التوابع الكمونية للدوران الداخلي للجزيئات تم اقتراح طريقة لتقدير التشوهات النسبية للجزيئات أثناء الدوران الداخلي، وخاصة من أجل الجزيئات التي تملك مستوي تناظر و زاوية وحيدة للدوران الداخلي j حيث تم استنتاج العلاقات التي تربط بصورة واضحة التغيرات النسبية للزوايا وأطوال الروابط بالمعاملات الفراغية شحنات و عزوم ثنائيات و رباعيات الأقطاب للذرات في الجزيئات وكذلك بزاوية الدوران الداخلي j. استخدمت نتائج الحسابات النظرية للشحنات وعزوم الذرات من أجل تقدير تشوه الزوايا والرابطة C –C في الجزيئات XCH2 – CH2X أثناء الدوران الداخلي حيثX = H, F, Cl, Br . تبين نتائج الحسابات بأن شحنات وعزوم الذرات المستخدمة تعتبر غير دقيقة . نوقشت التطورات اللاحقة لهذه النظرية و الطرق الحسابية المستندة عليها. On the basis of approximate quantum – mechanical theory of internal – rotational potential function of molecule has been suggested a method to evaluate relative deformation of molecule during internal rotation. In particular, for a molecules, which have a plane of symmetry and one angle of internal rotation j, have been derived an expressions that evidently, tie relative changes of angles and bonded distances with geometrical parameters, dipole and qudropole moments and charges of atoms in molecule, and also internal- rotational angle j. The results of theoretical calculation of charges and moments of atoms were used to evaluate of deformation anglesand distances C–C in molecules XCH2 – CH2 X during internal rotation, where X = H, F, Cl, Br. The results of calculation show that moments and charges of atoms in molecule, which using ,are not accurate. The subsequent development of this theory and theoretical calculation methods have been discussed.